Pyoderma gangrenosum. A case report - Elizabet Fernández López; Adialys Acosta Rodríguez; Daymí Martínez Rodríguez; Yanet Fragoso Cordero (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
Pyoderma gangrenosum is a rare inflammatory disease of unknown etiology characterized by sterile neutrophilic infiltration of the dermis, which may or may not be associated with systemic disease. Its classic description is the presence of one or more ulcerated skin lesions, painful, with an infectious appearance, irregular edges, undermined and with an excessive response to local trauma called pathergy. The case of a 58-years-old patient is presented, with skin lesions of two months' evolution and several previous treatments without improvement. Upon reassessment, her case was diagnosed and treated as pyoderma gangrenosum with satisfactory evolution.